2008
DOI: 10.1089/aid.2008.0051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of HIV Type 1 in Newly Diagnosed Patients in Southern Spain

Abstract: The prevalence of different HIV-1 subtypes in Spain varies by geographic region. In the present study isolates were collected from 72 newly diagnosed individuals in western Andalucia from 2004 to 2006. Viral sequences were amplified and the subtype diversity and prevalence of resistance mutations in the reverse transcriptase and protease genes were determined. The results presented here demonstrate that subtype B virus predominates in this region (88.9%), with the non-B subtypes CRF02_AG (9.7%) and B/G (1.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
4
2
Order By: Relevance
“…The results presented confirmed that subtype B is still the main HIV-1 variant in Spain, as reported previously for the same sample of subjects from CoRIS (16), and are concordant with data from other Spanish studies (23,31,34). What our study adds is the finding that 8.8% of the 670 CoRIS patients (14% of the 164 patients assessed in 2008) were infected with HIV-1 recombinant variants (CRFs and URFs) and the description of the genetic nature of the complex recombinants.…”
Section: One Of 10 Hiv-1-infections In Spain Could Represent Recombinsupporting
confidence: 92%
See 1 more Smart Citation
“…The results presented confirmed that subtype B is still the main HIV-1 variant in Spain, as reported previously for the same sample of subjects from CoRIS (16), and are concordant with data from other Spanish studies (23,31,34). What our study adds is the finding that 8.8% of the 670 CoRIS patients (14% of the 164 patients assessed in 2008) were infected with HIV-1 recombinant variants (CRFs and URFs) and the description of the genetic nature of the complex recombinants.…”
Section: One Of 10 Hiv-1-infections In Spain Could Represent Recombinsupporting
confidence: 92%
“…The highest prevalence of recombinants was found in patients from sub-Saharan Africa, followed by Eastern Europeans. As previously reported in the initial CoRIS description (16) and in other studies (23,24,31,34), recombinant CRF02_AG was the most frequently found HIV-1 non-B variant in our country, accounting for more than one-third of HIV-1 non-B infections. This is due to the high prevalence of this recombinant in Central and West Africa, the most common origin of infected sub-Saharan Africans residing in Spain.…”
Section: One Of 10 Hiv-1-infections In Spain Could Represent Recombinsupporting
confidence: 85%
“…The prevalence of the different HIV‐1 subtypes in Spain varies geographically. Although our results are similar to those reported in Madrid (18% of newly diagnosed HIV‐1–positive patients were infected with non‐B subtypes), they are not concordant with data from other Spanish regions (11% in southern Spain and 36% in northwestern Spain) . With regard to the situation in the overall European population, Abecasis and colleagues found that 33.9% of patients with newly diagnosed HIV‐1 in Europe during 2003 and 2005 presented with HIV‐1 non‐B subtypes.…”
Section: Discussioncontrasting
confidence: 63%
“…Although our results are similar to those reported in Madrid (18% of newly diagnosed HIV-1-positive patients were infected with non-B subtypes), 28 they are not concordant with data from other Spanish regions (11% in southern Spain and 36% in northwestern Spain). 9,29 With compartmentalized epidemics determined by the social and behavioral characteristics of the affected individuals. 8 In the United States, the reported rate of HIV non-B subtypes in blood donors is only 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent increase in immigration rates, the incidence of non-B variants circulating in Madrid (ϳ9%) during the period 2005 to 2007 has not increased in comparison with previously published data (32). Nevertheless, our phylogeographic analysis has revealed a very complex epidemiological scenario in all the subtypes studied in detail.…”
Section: Discussioncontrasting
confidence: 47%